2022
DOI: 10.1007/s42979-022-01172-3
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Voice Assistant Usability: An ISO 9241–11 Approach

Abstract: Voice assistants (VA) are an emerging technology that have become an essential tool of the twenty-first century. The VA ease of access and use has resulted in high usability curiosity in voice assistants. Usability is an essential aspect of any emerging technology, with every technology having a standardized usability measure. Despite the high acceptance rate on the use of VA, to the best of our knowledge, not many studies were carried out on voice assistants' usability. We reviewed studies that used voice ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 71 publications
(75 reference statements)
0
13
0
Order By: Relevance
“…The findings indicated that the proposed heuristics were more effective than Nielsen's heuristics and helped participants to identify more usability issues, especially concerning interaction design, human-like characteristics, dialogue content, help and guidance, and data privacy. Dutsinma et al (2022) identified the usability measures currently utilized for voice assistants through a systematic review. They identified a comprehensive list of usability measures, which included the measuring metrics of the ISO 9241-11 framework and additional outside measures.…”
Section: Usability Evaluation Methods Of Ai Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings indicated that the proposed heuristics were more effective than Nielsen's heuristics and helped participants to identify more usability issues, especially concerning interaction design, human-like characteristics, dialogue content, help and guidance, and data privacy. Dutsinma et al (2022) identified the usability measures currently utilized for voice assistants through a systematic review. They identified a comprehensive list of usability measures, which included the measuring metrics of the ISO 9241-11 framework and additional outside measures.…”
Section: Usability Evaluation Methods Of Ai Applicationsmentioning
confidence: 99%
“…In response, numerous researchers shared various ideas for future research. For instance, Dutsinma et al (2022) argued that the current ISO 9241-11 framework is not appropriate for measuring the usability of AI-based applications. It is not capable of clearly explaining machine voice, cognitive load, and attitude.…”
Section: Future Work and Research Directionsmentioning
confidence: 99%
“…First, the H1 of the study assumed a significant, direct effect of Artificial Intelligence on the Learning Management System that remained accepted with a significance level at p> .000. As noted by Lawal et al (Lawal et al, 2022),, Artificial Intelligence in online learning systems are widely facilitating student in many ways as it not only content but also helps the student to access the services they want, search the most relevant options, check their academic grades, and even maintain their profile and privacy in a best possible manner. Further, H2 of the study indicated a direct, significant relationship between Language Processing and Reasoning.…”
Section: Goodness Of Fitmentioning
confidence: 99%
“…When this happens, worries and doubts often lead patients to independently search for information on the Internet with every available tool [1,2]. VAs have recently joined the arsenal of devices that allow searching for information online [5,6] and, even if there are no studies yet, they are probably already widely used to obtain information on sexual health.…”
Section: Our Findings and Available Literaturementioning
confidence: 99%
“…They are designed to respond in natural language, simulating human conversation. VAs use the Internet to provide answers; however, they cannot be considered as simple "web search engines 2.0" since they are artificial intelligence (AI) [5,6]. VAs are integrated into smartphones, smart speakers, laptops, and desktops to help users in a variety of daily tasks or for entertainment purposes.…”
Section: Introductionmentioning
confidence: 99%